Symbolism Of Consciousness Toward Self Purgation In Ahmadun Yosi Herfanda's Poems - Sofiana, Anita (2016)
The objectives of the research are 1) to analyze the symbolism used in Ahmadun Yosi Herfanda's poems, 2) to analyze the narrative poem based on structural elements. The type of the research that is used by the researcher is qualitative research. The object of the research are the text of the works "River of Faith, Zikir of Ant, Poem of a Glass of Milk, Reflection of Range and Time, Poem of Cocoon, The Worshipping Grass, Tahajjud in Loneliness, Grave Visit in Memoriam, Moment of Dusk" by Ahmadun Yosi Herfanda. The data sources are The Worshipping Grass by Herfanda, are books, article, and virtual references. The results of the research show that Herfanda expresses his consciousness of self purgation through several characteristics of poetic expression in his five poems. Those characteristics are: 1) employing a simple idea structure written in easy understood word-choices of Islamic English; 2) employing numerous metaphors as the attractive way to attract the readers' curiosity in the process of understanding the poem's significance; 3) he uses several repetitions to arouse the readers' emotion in order to experience his sensitivity; and 4) he uses other texts in the form of written materials and life as the hypogram of the poem